Application of the Problem-Based Learning Model to Improve Learning Outcomes of Class VI Students of SD Negeri Kedungwaru - Hikmawati Hikmawati; Zulfan Zulfan; Tangdliman Tangdliman (Pascasarjana Universitas Mataram, 2022)
Every teacher expects all students to achieve mastery in learning above the Minimum Completeness Criteria (KKM). The learning outcomes of grade VI students of SD Negeri Kedungwaru have not reached maximum completeness, namely there are 12 children out of 26 children whose scores are above the KKM. This shows the need for efforts to improve student learning outcomes. The purpose of this community service activity is to improve the learning outcomes of grade VI students at SD Negeri Kedungwaru through the application of a problem-based learning model. The location for the implementation of the activity is at SD Negeri Kedungwaru, Prembun District, Kebumen Regency, Central Java. The time for carrying out activities in the classroom is carried out for 2 days, namely on August 26, 2022 and September 13, 2022. The number of participants in the activity, namely all sixth-grade students, is 26 people. The method of activity includes 3 parts, namely introduction, core, and closing. In the preliminary activities, apperception, motivation, and delivery of goals are carried out. In the core activities, 6 things are carried out namely orientation of students to problems, organizing students, guiding individual or group investigations, developing and presenting work, and analyzing and evaluating problem-solving processes. In the closing activity, concluding activities, learning reflections, and evaluations (giving tests) are carried out. The results of the activities show that: In learning 1 the average value of students from the aspect of knowledge assessment is 86.06, skills assessment is 85.58, while in learning 2 the average value of students from the aspect of knowledge assessment is 89.62, a skills assessment is 86.38. In the 1st and 2nd lessons, the value of all students has exceeded the KKM, with a KKM score of 70, so the number of students who have completed reached 100%, which is 26 students. From the aspect of assessing students' social attitudes in learning 1, 91% of students showed high curiosity, confidence and cooperation, and in learning 2 increased to 96%. Thus, community service activities in the form of applying a problem-based learning model can improve the learning outcomes of sixth graders at SD Negeri Kedungwaru in terms of knowledge, skills, and social attitudes.